(3GdOdGFd Ydi eYGfi GdMOjK HGdTGgO hGdeKds - (3bGSe Hf KGHJ Hf MRe GdYhaj GdSQbSWj, CHh eMeO,J (B302 (3g` s
(3ChdgG (B:s
(3hbGd ai MOjK GdfHi (B( (3Udi Gddg Ydjg hSde (B) (3Cfg CJi jYdGdI TGg aCcd efgG , Ke Udi hde jJhVC bhdg HYdGdI TGI jQjO HTF jSjQ cGf bO aVd efgG hbGd GdQGLR (B: (3CMed Cei hgj GdMeO dg JVQYfi GdOQI hGdYdGdI s
(3BNQgG (B:s
(3hbGd ai MOjK CHj eSYhO YbHI Hf YeQh GdCfUGQi (B: (3Efi dCOY GdCVMjI hCfG ef CjSQce cQGgjI Cf jYde GdfGS CfgGMJe hGLH hai bhd GHf eSYhO cQGgjI hcQGgI Cf jYde KdGK dZGJ (B: (3cQGgjI hcQGgI hcQGgjf CJjc cQGgjf Gf JZVH Je GdTQM jJdhg ai GdSaQ GdKGdKs
(3eGJ eDdaI bHd EJeGegs
(3hCcedg CHhg GdPi Jhai (B313 (3g` bGd CHh Ydi GdbGdi Yfg (B: (3Efg de jDda eKdI ai GdeZQH s
(3hbO Je CNP YfhGf gPg GdeNWhWI ef BNQ GdLRA GdKGdK ef GdfSNI faSgG hcPdc aYd GdRQcdi ai GdCYdGe (B174/5 (3GdPi PcQ gPg GdfSNI HLRFjgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B174s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs